Regression verification: proving the equivalence of similar programs. (21st March 2012) - Godlin, Benny; Strichman, Ofer
SUMMARY Proving the equivalence of successive, closely related versions of a program has the potential of being easier in practice than functional verification, although both problems are undecidable. There are three main reasons for this claim: (i) it circumvents the problem of specifying what the program should do; (ii) the problem can be naturally decomposed and hence is computationally easier; and (iii) there is an automatic invariant that enables to prove equivalence of loops and recursive functions in most practical cases. Theoretical and practical aspects of this problem are considered. Copyright © 2012 John Wiley & Sons, Ltd.